2003
DOI: 10.1007/s10006-002-0429-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimentelle Untersuchung zur biomechanischen Stabilität unterschiedlicher Unterkieferosteosynthesen

Abstract: Our fracture and osteosynthesis model allows the quantitative determination of micromovements in the gap tissue and shows the importance of ideal realignment, which has a decisive influence on micromovements in the gap tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although experimental studies on biomechanics have confirmed sufficient stability of the 3D plating system,[ 21 22 ] only a few clinical studies are reported in literature. [ 18 20 23 24 ] The use of 3D miniplates in mandibular fracture fixation has not yet become established.…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental studies on biomechanics have confirmed sufficient stability of the 3D plating system,[ 21 22 ] only a few clinical studies are reported in literature. [ 18 20 23 24 ] The use of 3D miniplates in mandibular fracture fixation has not yet become established.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies used three screws for xation; however, more than three screws were used in the distal and proximal stumps in our study. [11] , [12] , [13] Signi cant stresses occurred at the screw attachment-bone interfaces during chewing, and screw loosening may develop as a long-term complication after mandible reconstruction with plates. [14] , [15] ,…”
Section: Discussionmentioning
confidence: 99%
“…This potentially implies that, compared to reconstruction and compression plates, a thinner design or reduction in plate cross-section with fewer number of screws per fracture side may be established, even by using monocortical fixation [15]. According to some authors, this may need to be compensated by a higher plate thickness or different plate geometry to achieve sufficient immobilization [16][17][18][19][20]. However, there is still no consensus on the indication and predictability of outcomes with regards to the use of three-dimensional plates for mandibular angle fractures.…”
Section: Introductionmentioning
confidence: 99%